Evaluation of working memory impairment in children with primary nocturnal enuresis: Evidence from event-related functional magnetic resonance imaging - Yu, Bing; Guo, Qiyong; Fan, Guoguang; Ma, Hongwei; Wang, Lu; Liu, Na (Journal of paediatrics and child health, 2011)
Aim:  To assess the working memory and explore the differential activations of brain areas in children with primary nocturnal enuresis (PNE) by performing functional magnetic resonance imaging (fMRI) scans using the categorical N‐Back task. Methods:  Thirteen right‐handed PNE children (M/F = 7:6, average age 11.4 ± 0.8 years) and 15 age‐matched, right‐handed, healthy controls (M/F = 9:6, 11.3 ± 1.0 years) were recruited for the study. First, intelligence tests were performed using Chinese Wechsler Young Children Scales of Intelligence in PNE children and controls. The full intelligence quotient (FIQ), verbal IQ (VIQ), performance IQ (PIQ) and memory/caution (M/C) factor were measured. After intelligence tests, event‐related fMRI scans were performed using the categorical N‐Back working memory task on a 3.0T MR scanner. The percent of correct responses (PCR) and the mean reaction time to correct response (mRT) were recorded and compared; fMRI data were analysed using SPM2, the differences in activation were compared with the single subject and between‐group levels. Results:  The FIQ, VIQ and PIQ in the PNE group were within the normal range and did not significantly differ from the control group (P > 0.05). The M/C factor was statistically significantly lower in the PNE group (P < 0.05). In the N‐Back test, PNE children had lower PCR and longer mRT than controls (P < 0.05). A between‐group analysis of fMRI data revealed significant attenuation in the left posterior cerebellar lobes of PNE children. Conclusion:  PNE children had deficits in working memory, and dysfunction in the left cerebella might be associated with their working memory deficits.